EFFECT OF YOGIC PRACTICES AND DIET MODIFICATION ON LDL AMONG HYPERTENSIVE MIDDLE-AGED WOMEN - Shinu Patinhara Malammal; Saheedha A; Sunil Alphonse; Sanith N V; Sudheesh V S; Hemalatha V (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
The present random group experimental study was designed to find out the effect of yogic practices on LDL (low density lipoprotein) among hypertensive middle-aged women. It was hypothesized that there would be significant difference on LDL (low density lipoprotein) among hypertensive middle-aged women due to yogic practice than the control group. To achieve the purpose of the study, forty five (N=45) hypertensive middle aged women residing in Kozhikode city aged between 35 to 45 were selected randomly and divided into three equal groups and named Yoga group ( n=15), Yoga and Diet group ( n=15) and control group (n=15). Training period of the study was six weeks, six days of practice in one week and each session duration is maximum one hour in the morning. The control group was kept in active rest. Pre-test and post-test were conducted for Experimental and control group before and after the training programme using LDL test in laboratory. Statistical analysis has been done using t test to find out differences between the groups. It was concluded that there was significant reduction in LDL (low density lipoprotein) of the group which underwent yogic practices and diet control and yogic practice group than the control group.